Diseño e implementación de un sistema de riego por goteo para pimiento (capsicum annuum l.) en el área convencional, ESPAM-MFL. - Intriago Vidal, Andrés Bolìvar (2012)
This research study was based on the Design and Implementation of Drip Irrigation for pepper (Capsicum annuum L.) in the conventional area of the ESPAM – MFL, during the months of October 2011 to February 2012. Having done the calculations of Hydraulic Design by Blasius formulas for optimal management and system design to meet Agricultural water requirements of the pepper crop was obtained the following results on the hydraulic flow required for emitter side or holder is 189 L/h and pressure of 14.524 psi required. The flow required for a lateral slide third was 11718 L/h and the commercial diameter of the pipe is 47.20 mm the appropriate pressure used in this module was 16.905 psi, the conduit is installed on 63 mm diameter was determined by calculations previously made, it will serve as driving to another peer with the same hydraulic characteristics. For the design was considered agronomic climatic conditions by averaging the crop water needs and readily available water supplies for growing pepper determining that the irrigation intervals are every 1.5 days and the run time is 51.40 minutes per day in their respective periods. Costs incurred in designing and implementing of the irrigation system is $ 2519.92, including labor and incidentals.